Deconstructing Indonesian film for Semarang’s city branding as a cinematic city - Amida Yusriana; Mutia Rahmi; Mukaromah Mukaromah (Masyarakat, Kebudayaan dan Politik, 2018)
The Variety of Culture is the current city branding concept for Semarang City. It depicts the various cultures and ethnicities that live together in Semarang. However, this city branding is considered insufficient to meet the tourism target. This research aims to develop a new branding for Semarang as a Cinematic City. This concept is derived from the success of several cities which famous as shooting locations, for example Oxford in England, Seoul in South Korea, and New Zealand as the filming sites of The Lord of the Rings. The main aim of this research is to map out the potential locations for Semarang’s new branding as a Cinematic City. This research is conducted for three popular movies: Gie, Ayat-Ayat Cinta and Soekarno which those movies used Semarang City as the major filming sites. The result found there are three separated areas in Semarang that can be built as the main points of the city branding. Specifically located in the Old Town District there are Srigunting Park, State Financial Building, Cockfighting site, Berok Bridge, Blenduk Church, Jakarta Lloyd Building, and Berok River. In total, there are nine locations that can be developed as a tourism hub which served as a brand attributes of the effort to construct a Semarang as a Cinematic City. In conclusion, some areas have the potential to be developed into the object of city branding Semarang those are Kota LamaDistrict, Imam Bardjo Auditorium University of Diponegoro and Lawang Sewu Building.